Mycobacteria–host interactions in human bronchiolar airway organoids. Issue 3 (5th November 2021) - Iakobachvili, Nino; Leon‐Icaza, Stephen Adonai; Knoops, Kèvin; Sachs, Norman; Mazères, Serge; Simeone, Roxane; Peixoto, Antonio; Bernard, Célia; Murris‐Espin, Marlène; Mazières, Julien; Cam, Kaymeuang; Chalut, Christian; et al.
Abstract: Respiratory infections remain a major global health concern. Tuberculosis is one of the top 10 causes of death worldwide, while infections with Non‐Tuberculous Mycobacteria are rising globally. Recent advances in human tissue modeling offer a unique opportunity to grow different human "organs" in vitro, including the human airway, that faithfully recapitulates lung architecture and function. Here, we have explored the potential of human airway organoids (AOs) as a novel system in which to assess the very early steps of mycobacterial infection. We reveal that Mycobacterium tuberculosis (Mtb) and Mycobacterium abscessus (Mabs) mainly reside as extracellular bacteria and infect epithelial cells with very low efficiency. While the AO microenvironment was able to control, but not eliminate Mtb, Mabs thrives. We demonstrate that AOs responded to infection by modulating cytokine, antimicrobial peptide, and mucin gene expression. Given the importance of myeloid cells in mycobacterial infection, we co‐cultured infected AOs with human monocyte‐derived macrophages and found that these cells interact with the organoid epithelium. We conclude that adult stem cell (ASC)‐derived AOs can be used to decipher very early events of mycobacteria infection in human settings thus offering new avenues for fundamental and therapeutic research. Abstract : Flowchart of host–pathogen interactions in microinjected human bronchiolar airway organoids. Organoids were injected using a micromanipulator coupled to a microinjection system (left). The capillary was pushed into the lumen of airway organoids (AOs) to deliver mycobacteria (middle). The readouts used to study host–pathogen interactions within the organoids are summarized (right). Created with Biorender.com.